Body Weight and Gender Differences in Nutritional Status of Toddler According to WHO and CDC References: A Study from Taud Al-Hanif Jombang - Lestari, Rini Hayu; Prihartanti, Niken Grah (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Efforts to reduce the prevalence of wasting and stunting are urgently needed. Research on differences in nutritional status and growth of toddlers based on gender and weight can provide important insights into how nutrition interventions and health policies can be tailored to meet the specific needs of these groups. Several studies have shown that boys and girls may have different nutritional needs and may experience different growth rates. In addition, each stage of toddler age also has unique growth characteristics and nutritional needs.This study used a comparative analytical design with a cross-sectional approach. This design was chosen to evaluate differences in nutritional status and growth of toddlers based on gender and weight at a certain time. The population in this study were all children aged 13-59 months at TAUD Al Hanif in 2023. The sample of this study was taken from the population using a stratified random sampling technique. Data collection was carried out using a digital scale instrument, staturemeter, and questionnaire form. The measurement results showed that there were significant differences between the nutritional status of toddlers based on weight and gender as evidenced by the value (p <0.05). Toddlers with normal weight tend to have better nutritional status, while toddlers who are underweight or overweight need special attention. Male toddlers are more likely to have good nutritional status than female toddlers, which may be due to differences in nutritional needs and socio-cultural factors. Appropriate nutritional interventions need to be carried out to ensure that all toddlers, both boys and girls, receive adequate nutrition for optimal growth and development.